PENGARUH MODEL PROJECT BASED LEARNING DENGAN STRATEGI BERDIFERENSIASI TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA DI SMA - br Ginting, Delfi Anggriana; Purba, Glory Indira Diana (MES: Journal of Mathematics Education and Science, 2024)
The research was conducted to find out how the project-based learning model with differentiated strategies has an influence on students' critical thinking skills. The study population was all X grade students totalling 11 classes at SMA Negeri 1 Sunggal. The sample used in this study amounted to 62 students with purposive sampling method and divided into two groups, namely the experimental group and the control group. While the experimental group, class X-3, applied differentiated strategy with Project Based Learning model, the control group, class X-2, used conventional learning. The results showed that students' critical thinking writing skills were significantly influenced by the project-based learning model with differentiated strategies. This can be seen from  (4.517)  (1.670). The contribution of the role of the Project Based Learning model with differentiated strategies is high, it can be seen in the effect size value which shows a contribution of 1.1472.